P643 Adverse pregnancy and neonatal outcomes associated with neisseria gonorrhoeae: a systematic review and meta-analysis. (14th July 2019) - Egli-Gany, Dianne; Vallely, Lisa; Wand, Handan; Vallely, Andrew; Low, Nicola
Abstract : Background: Neisseria gonorrhoeae (NG) infections during pregnancy have been reported to be associated with a range of adverse pregnancy outcomes, but systematic information is lacking. The objective of this study was to systematically review data about associations between NG and: preterm birth (PTB); low birth weight (LBW); premature rupture of membranes; spontaneous abortion; perinatal mortality; and ophthalmia neonatorum. Methods: We searched Medline, Excerpta Medica, Cochrane Library and the Cumulative Index to Nursing and Allied Health Literature databases up to October 2017. Two researchers selected studies, extracted data and assessed risk of bias independently. We used meta-analysis to calculate summary odds ratios (OR with 95% confidence intervals, CI) separately for unadjusted and adjusted results, stratified by study design. We assessed heterogeneity using the I 2 statistic. Results: We screened 2, 290 articles and included 15 studies, published from 1976–2017, of which seven were from low or lower-middle income countries. For PTB, the summary unadjusted OR was 1.47 (95% CI 1.17–1.78, I 2 =0%) in four case-control studies, 1.93 (1.24–2.63, I 2 =86%) in two cross-sectional studies and 0.78 (0.49–1.06, I 2 =0%) in three cohort studies. Adjusted ORs were only available in three case-control studies, summary OR 1.14 (0.85–1.44, I 2 =16%). For LBW, the summary unadjusted OR was 1.57 (1.15–1.99, I 2 =53%) in three case-control studies, 1.20 (0.30–4.30) in one cross-sectional study and 0.99 (0.73–1.25, I 2 =47%) in two cohort studies. The adjusted summary OR was 1.33 (0.96–1.71, I 2 =0%) in the case-control studies. For other outcomes, unadjusted summary ORs varied, generally being lower for cohort than cross-sectional or case-control studies. Conclusion: In this systematic review of observational studies, the strength of associations between NG and adverse pregnancy outcomes were weaker than expected and, where data were available, attenuated after adjusting for confounding. Ongoing randomised controlled trials will now determine whether screening and treatment of NG in pregnancy reduces adverse outcomes. Disclosure: No significant relationships.